PROBING RHETORICAL STRUCTURES OF ADVANCED LEARNERS’ EXPOSITORY PROSE: A DATA-BASED APPROACH - Marcellinus Marcellino (Indonesian JELT, 2007)
Logic, as the basis of rhetoric, always affects the way ideas, words, and evidence are assembled into one coherent structure. As rhetoric varies from culture to culture, it frequently brings about awkwardness, inappropriateness as well as immaturity of an expository prose if it does not meet the convention of organizational patterns  and signals as expected by the readers having that rhetoric. A number of scholars have highlighted the importance and insights of contrastive rhetoric for the teaching of academic writing. This paper describes various rhetorical problems encountered by dozens of advanced Indonesian learners of English taking an academic writing class at AMINEF (American Indonesian Exchange Foundation) who plan to study in the USA. This paper concludes with the caveat that difficulties in adopting English rhetoric is not simply  a linguistic problem but includes cultural understanding and awareness of its style. This paper offers insightful writing instructions to cope with the existing problems. Keywords: rhetoric, expository prose, contrastive rhetoric, rhetoricalproblems, AMINEF